THE ANALYSIS OF THE MEANING OF HOME FOR IMMIGRANTS IN THE ESCAPE USING STUART HALL REPRESENTATION THEORY - Eka Putra, Aldi Fahrizal; Sriastuti, Anna (Universitas Respati Yogyakarta (UNRIYO), 2025)
For a lot of people, home is a place that serves the purpose only to gather and take a rest. But, for immigrants, especially one that lives away from their birthplace, home is something that they always miss a lot, since they live far away from their homeland. For Moslem, they have certain events where they are able to go back to their home and it is called Eid Al-Fitr. There is something about the way Samir finds the meaning of home through the journey that he must do to escape from his trauma due to the death of his wife. In order to find the actual meaning of home, Representation Theory by Stuart Hall will be applied in this research by understanding the way Samir see’s home. The result from this research will provide readers about the actual meaning of home, whether home is a place to take a rest or about where someone's heart belongs too.